Instructional Competence of the Elementary Teachers: Investigating the Multidimensional Knowledge Framework - Uddin , Perona; Usman, Cecilia; Ticzon, Amina; Sukarno, Jikiron (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to assess the teaching competencies of elementary school teachers from grades 4 to 6 in a digital classroom setting, specifically examining their proficiency across the triad of content knowledge, pedagogical knowledge, and technological knowledge.   A researcher-designed survey instrument was utilized and administered to thirty teachers from two elementary public schools. The survey measured competency across the three key areas. Results demonstrated high levels of competency across all three domains, with mean scores of 4.42 for content knowledge, 4.35 for pedagogical knowledge, and 3.61 for technological knowledge. The correlations between these competency scores and years of teaching experience and highest educational attainment were non-significant (p > 0.05). Complete demographic data was provided by all thirty participants with 100% response rate. These findings suggest that high competency levels are present regardless of experience or educational background within this sample of teachers from the two public elementary schools. Further research is needed to explore contributing factors and the generalizability of these results to broader populations. A prospective study tracking student academic performance, correlated with the previously assessed teacher competency scores, is required to establish a robust correlation between teacher skills and sustained student achievement within digital learning environments.  In conclusion, while this study indicates high teacher competency in the selected schools, further research is necessary to confirm these findings in more diverse settings and to better understand the relationship between teacher skills and student outcomes.
Keywords: Competency, digital classroom, elementary teachers, Pedagogy, Technology